The Experience of Home and Dwelling in Women's Writing - Zubíková, Radka (Univerzita Pardubice, 2015)
The aim of this bachelor paper is to provide an analysis of attachments the child protagonists have to a house/home. For the analysis the following novels were chosen: The Secret Garden by Frances Hodgson Burnett, Mandy by Julie Andrews Edwards and Abela: The Girl Who Saw Lions by Berlie Doherty. The theoretical part outlines the concepts concerning the experience of space and place, particularly the human experience of home and its loss as introduced by Gaston Bachelard, Martin Heidegger and Yi-Fu Tuan. The analytical part explores the ways the child characters experience a sense of home, its loss and the feelings of uprootedness when forced to leave their homeland. The work further focuses on a journey of the protagonists towards finding a family and a new home to live in.
Prožitek domova a bydlení v literatuře psané ženami
Keywords: homes; houses; places; experience; loss of home; domovy; domy; místa; prožitek; ztráta domova